Spawning observations of Pomadasys commersonnii in the marine section of the Knysna estuarine bay, Western Cape, South Africa. Issue 1 (2nd January 2022) - Butler, EC; Childs, A-R; Smith, MKS; Foster, RM; Potts, WM
Abstract : Knowledge of the location and timing of spawning events is critical for fisheries management. As is the case for many southern African fishes, the spotted grunter Pomadasys commersonnii was historically thought to reproduce in the coastal waters off KwaZulu-Natal Province (KZN), South Africa, with subsequent egg and larval dispersal towards the Eastern Cape (EC) and Western Cape (WC) provinces facilitated by the Agulhas Current. More recently, year-round residency within areas of the EC and the observation of reproductively mature individuals in certain WC estuaries has provided some support for spawning events southwest of KZN. This study reports empirical evidence of active spawning in the sheltered marine section of the Knysna estuarine bay, WC. Observations of spawning behaviour were noted during large aggregations of adult fish over shallow sandbanks in February 2017. A single male and female were collected, and their reproductive organs were macroscopically staged as 'spawning.' Gonad histological examination verified active spawning of the female via the presence of hydrated oocytes, migratory nucleus oocytes and post-ovulatory follicles. Future research should focus on the identification and conservation of critical spawning events and investigate the potential role of large marine-dominated estuarine systems in the life history of this and other marine estuarine-dependent species. Lastly, the results of this study contribute towards a knowledge base that challenges the traditional theory of northeastward spawning migrations as the sole life-history strategy for numerous South African fishery species.